MODERN CONTRACT LAW: DYNAMICS OF AGREEMENTS IN THE ERA OF ECONOMIC DIGITALIZATION - Adnan Lira; St Hatidja (Leges Privatae, 2026)
The digitalization of the economy has revolutionized the way humans interact legally, particularly in the formation and implementation of agreements. The rapid development of information technology has given rise to new transaction models that cannot always be adequately accommodated by the Civil Code (KUHPerdata), which was created in the 19th century. This article examines in depth the dynamics of the transformation of contract law in the context of economic digitalization, including aspects of the validity of electronic contracts, the legal status of blockchain-based smart contracts, consumer protection in the digital trade ecosystem, and the challenges of jurisdiction and choice of law in cross-border digital transactions. Using normative legal research methods through statutory, conceptual, and comparative law approaches, this study concludes that Indonesia's contract law framework requires systemic modernization that includes formal recognition of algorithmic contracts, revision of the concept of agreement in the context of digital interfaces, strengthening the principle of proportionality in electronic adhesion contracts, and establishing a dispute resolution mechanism that is responsive to the unique characteristics of digital transactions. Recommendations include the establishment of a comprehensive national contract law, strengthening technical regulations in the field of electronic signatures, and harmonizing the law with international standards UNCITRAL.